Media Pembelajaran sebagai Pembawa Pesan - Ida Nur'aini (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
Education technology is as important as the education itself. Education technology speaks more than just supporting devices for learning. It is actually a systematic way of designing, implementing, and evaluating the total process of learning and teaching in terms of specific objective. Based on research in human learning and communication, education technology employs a combination of human and nonhuman resources to bring about more effective instruction. The main issues of education technology lie on technology capability to deliver education messages. Some factors need to be addressed: communication obstacles, kinds of media, new media research for education purposes, institutional support as well as public policy support.